A Review of Contemporary Islamic Legal Philosophy Towards the Orientation of Iddah Legislation: Tinjauan filsafat Hukum Islam Kontemporer Terhadap Orientasi Pensyariatan Iddah - Alfiandri Setiawan; Ahmad Kamalul Fikri (Institut Agama Islam Negeri Fattahul Muluk Papua, 2024)
The polemics over the phenomenon of people marrying and divorcing often requires a transitional period to evaluate marriage after the occurrence of adivorce The purpose of this study is to conduct a philosophical understanding of the orientation of iddah legislation. This research uses the perspective of maqasid sharia development formulated by Jaser Auda as the theory of analysis. The results of the study concluded that there are several axiological aspects of the iddah ordinance, including health protection and regeneration. This is because iddah has a positive impact on maintaining the health of women's reproductive organs. This understanding can be said as a form of value expansion of the concept of hifz nafs (protecting the soul) and hifz nasl (protecting offspring). Then, as self-introspection. This is because iddah is important to be a time of reflection for men and women in evaluating themselves, to reconcile again or separate amicably. This understanding can be said as a form of expansion of the value of the concept of hifz aql (protecting the mind). Furthermore, as a period of mourning for the death of the husband. This is because marriage is not just a contract, but also a serious agreement. This understanding can be said to be a form of value expansion from the concept of hifz al-'ird (maintaining social ethics). Next, as a protection of religious teachings. This is because carrying out iddah is an obedience to Islamic teachings. This research shows that the provision of iddah has complex axiological aspects.